A Shift Of Legal Entity Company Created With Authentic Deedin Form Of Limited Liability Company And The Birth Of Individual Company Created Without Authentic Deed - Mar’ie Muhammad Setianegara; Hasim Purba; Suprayitno, Suprayitno (SEAN Institute, 2024)
The sole proprietorship as a new profit legal entity in Indonesia brings a new concept to the world of companies in Indonesia. As with the establishment of a sole proprietorship without an authentic deed organized by a Notary, this is different from the concept of establishing a limited liability company that uses a deed of establishment by a Notary. This thesis analysed the shift in the establishment of a sole proprietorship legal entity without an authentic deed, which is different from the establishment of a limited liability company with an authentic deed. The formulation of the problem in this study is: Does a sole proprietorship have elements as a legal entity according to legal theory and legal doctrine; Why is the establishment of a sole proprietorship legal entity carried out without an authentic deed, which is different from the establishment of a limited liability company that must be established with an authentic deed; how is the legal force for proving the certificate of establishment of a sole proprietorship issued by the Ministry of Law and Human Rights. The research method used in this study is a normative legal research type, which is supported by primary and secondary legal sources and is analysed qualitatively. The results of the research and discussion are that a sole proprietorship as a new legal entity, reviewed from the theory of legal entities, fulfills the elements of a legal entity against a sole proprietorship, but when reviewed from the legal doctrine by Nindyo Pramono, a sole proprietorship does not have articles of association approved by the Minister, this is contrary to Nindyo Pramono's opinion. If this happens, the injured party can cancel the certificate of establishment of the sole proprietorship at the State Administrative Court.